Pregnancy with Hepatoblastoma - Hermin Sabaruddin; Bambang Abimanyu; Muhammad Robyanoor Ahyadi Radam; Ruth Widhiati; Pribakti Budinurdjaja; Yosef Dwi Cahyadi Salan; Agatha Vamela (Fakultas Kedokteran Universitas Lambung Mangkurat, 2025)
Congenital hepatoblastoma is a rare primary liver malignancy that most commonly occurs in newborns with a prevalence of 1.2 -1.5 per million children per year. The etiology of congenital hepatoblastoma is unclear. Congenital hepatoblastoma is diagnosed in the fetal period and 3 months after birth. The ultrasound image revealed a heterogeneous hyperechoic mass in the liver lobe with clear boundaries and when the baby was born there was a clinical mass in the stomach, increased SGOT and SGPT and direct, indirect and total bilirubin and. Gold Standart diagnosis is based on histopathological examination. This study is a Case Report. A women 24 years old , 39-40 weeks gestasional age came PONEK Ulin Hospital with in labor. Patient came in condition active phase of labour with history of labor spontan vertex delivery. There is no congenital abnormalities history of family. During antenatal care, US at 35 weeks gestasional age result congenital anomaly regio abdomen suspected mesenterial mass. Baby born spontaneous delivery Male/2845g/47cm/AS 8-9-10 and do neonatologist evaluated US Lobus Hepar sinistra size 6.2 x 3.7cm susp hepatoblastoma and intraabdominal organs within normal limits. Laboratory result was SGOT and SGPT 106/26 ul, AFP >2000.00ng/ml, Bilirubin direct /indirect /total 0.9/10.9/11.9 mg/dl and FNAB result round cell tumor.Congenital hepatoblastoma is a rare primary malignancy of the liver in newborns and causes minimal complications during pregnancy but has severe consequences after birth. Postnatal treatment with surgery, chemotherapy and liver transplantation according to the severity of the hepatoblastoma lesion.